Active load control of large wind turbines using state-space methods and disturbance accommodating control. (1st May 2018) - Novaes Menezes, Eduardo José; Araújo, Alex Maurício; Rohatgi, Janardan Singh; González del Foyo, Pedro Manuel
Abstract: The control of wind turbine loads is fundamental to reduce wind energy cost. Wind turbines are complex dynamic systems subjected to random wind loads and harsh operational vibrations. Active load control reduces wind turbine mechanical vibrations, provoking an increase in wind turbine components lifetimes and the design of lighter and more flexible parts, reducing wind turbine global cost. The pitch control system plays a decisive role in shaping the wind turbine dynamics. By using the appropriate control methods, it can be used to reduce the dynamic response in most of wind turbine components, given the fully-coupled system dynamics. In this paper, it is demonstrated the development of an active load control of the wind turbine tower loads using the pitch control system. State-space control is carried out to consider the coupled wind turbine dynamics and the disturbance accommodating control (DAC) is used to cancel the effect of wind disturbances in the dynamics of the overall system. The active load control is performed without damaging the aerodynamic power control. Highlights: An active load control for wind turbines is developed using pitch control system. The control design and dynamic modeling is presented for a large-scale wind turbine. Control objectives include the reduction of tower vibrations and rotor speed control. Full non-linear simulations are performed to prove the effectiveness of the method.